Boardroom realities : (Jossey-Bass, 2009)
There is renewed interest in new boardroom practices that aim to strengthen the leadership role of directors. This book assembles the biggest names in the study of board governance as well as corporate board members themselves to address the critical questions that corporate boards face today.